Serine/Threonine Protein Kinase-3 Promotes Oral Squamous Cell Carcinoma by Activating Ras-MAPK Mediated Cell Cycle Progression - Yue L; Xu Y; Lu P (International Journal of General Medicine, 2023)
Li Yue,* Yuedi Xu,* Ping Lu Department of Stomatology, Liaocheng People’s Hospital, Liaocheng, Shandong, 252000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ping Lu, Department of Stomatology, Liaocheng People’s Hospital, Liaocheng, Shandong, 252000, People’s Republic of China, Tel +86 17763517077, Email 17763517077@163.comPurpose: Serine/threonine protein kinase-3 (STK3) is a key molecule in the Hippo pathway, but its biological function in the development of oral squamous cell carcinoma (OSCC) remains unclear, we explored the roles of STK3 in OSCC.Methods: In this study, GEPIA was used to analyse STK3 expression in different types of tumor patients. OSCC patients were then collected from Liaocheng People’s Hospital (Shandong, China), to further detect STK3 expression by qRT-PCR and Western blotting. To explore the function of STK3, overexpression and knockdown experiment were designed. Cell proliferation, migration and invasion were analyzed.Results: First, STK3 is significantly up-regulated in OSCC patients, and high STK3 expression is associated with poor prognosis. Then, in vitro cell proliferation, migration, and invasion tests were used to determine the role of STK3. STK3 overexpression significantly promoted the proliferation, migration and invasion of OSCC cells. The downregulation of STK3 inhibited the proliferation, migration and invasion of OSCC cells. Finally, STK3 was demonstrated to promote oral squamous cell carcinoma by activating Ras-MAPK mediated cell cycle progression.Conclusion: The results showed that STK3 was a potential cancer promoter for OSCC. It plays an important role in promoting the progression of oral squamous cell carcinoma. Inhibition of STK3 may prove beneficial as a therapeutic strategy for OSCC treatment.Keywords: oral squamous cell carcinoma cancer, OSCC, serine/threonine protein kinase-3, STK3, proliferation, migration, invasion